Discourses Related to the Activities of Local Offices in the 16th—18th Centuries (The Case of Upper Silesia) - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
A method of discursive analysis of archival official texts offers a comprehensive view of historical material, much more in-depth than stylistic analyses. The subject of this description are Polish-language official records created in Upper Silesia between the 16th and 18th centuries, illustrating a certain stage of the formation of institutional legal discourse, present in the Polish communicative space since the Middle Ages. The surviving collections represent various types of discourse, determined by the intentions of the people approaching the office and by the role assumed by the institutional entity both in a specific event and in the formulation of a legal written document. The article outlines the two most common discourses in the collections studied: 1. the chancery discourse, that was aimed to produce documentation that would ensure the approaching parties the right to dispose of property in accordance with the established agreements and financial transaction; 2. the judicial discourse, that involved resolving disputes between community members and ensuring public order. The written forms documenting the actions of the court served a mainly informative and reporting function, and their role was extremely important in the current legal system, as they formed the basis for possible appeal proceedings.